2012
DOI: 10.1590/s0100-69912012000600013
|View full text |Cite
|
Sign up to set email alerts
|

Análise da diversidade da microbiota intestinal de ratos submetidos à ressecção da valva ileocecal e criação de esfíncter artificial

Abstract: ileocecal resection led to changes in ileal microbiota and, with the creation of new sphincter, the changes were even greater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…There was alteration of the intestinal microbiota only in resected ileocecal valve group, that was greater in the terminal ileum than in the colon.In this study, was found an increase in the thickness and inflammatory infiltrate in the colon of GII animals. The microbiota alterations demonstrated by Barra et al 2 may be correlated to this finding. Saad et al 16 observed that extended intestinal resection did not determine significant weight loss after 60 postoperative days compared to control.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…There was alteration of the intestinal microbiota only in resected ileocecal valve group, that was greater in the terminal ileum than in the colon.In this study, was found an increase in the thickness and inflammatory infiltrate in the colon of GII animals. The microbiota alterations demonstrated by Barra et al 2 may be correlated to this finding. Saad et al 16 observed that extended intestinal resection did not determine significant weight loss after 60 postoperative days compared to control.…”
Section: Discussionmentioning
confidence: 59%
“…Barra et al 2 studied the consequences of ileocecal valve resection without enterectomy in intestinal microbiota. There was alteration of the intestinal microbiota only in resected ileocecal valve group, that was greater in the terminal ileum than in the colon.In this study, was found an increase in the thickness and inflammatory infiltrate in the colon of GII animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research has indicated that terminal ileum could be the main place where bacterial translocation occurs, due to ileocecal reflux under intestinal ischemia/reperfusion conditions [31, 32]. Therefore, ileostomy may prevent bacterial translocation besides having the merits of minimal trauma.…”
Section: Discussionmentioning
confidence: 99%